-11.2+4(2.1+q)=

Simple and best practice solution for -11.2+4(2.1+q)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11.2+4(2.1+q)= equation:


Simplifying
-11.2 + 4(2.1 + q) = 0
-11.2 + (2.1 * 4 + q * 4) = 0
-11.2 + (8.4 + 4q) = 0

Combine like terms: -11.2 + 8.4 = -2.8
-2.8 + 4q = 0

Solving
-2.8 + 4q = 0

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '2.8' to each side of the equation.
-2.8 + 2.8 + 4q = 0 + 2.8

Combine like terms: -2.8 + 2.8 = 0.0
0.0 + 4q = 0 + 2.8
4q = 0 + 2.8

Combine like terms: 0 + 2.8 = 2.8
4q = 2.8

Divide each side by '4'.
q = 0.7

Simplifying
q = 0.7

See similar equations:

| 0.71-.22s=1.03-0.625s | | 7x+3=28 | | -5(7p+20)=8+17p-16p | | 18-2x=-(-1-3x)-8 | | 22.8-2p=444 | | 6(h+4)=-2l | | 9w+14w+18=-8(-9w+20)-18 | | -(4n+6)+8=-6(n+1)2n | | (n+3)(8n+1)=0 | | 7.5x^2-6x-9.8=0 | | -3j=7(-4j+20)+18j | | R-9=-5 | | -4(-7z+16)=7(3z+15)+20z | | -(9-3x)=11 | | 0.20(y-6)+0.06y=0.18y-0.03(30) | | -4-6k+6-8=-6-6k | | (2x)+3=(4x)-3 | | 8(4k+1)=15k+6(10k-13) | | 6t^2-26t+22=0 | | 0.75x+5y=20 | | 8x-3x^2+2x= | | 12x+20=-40 | | (-1x)+2=2+(-4x) | | -4s=-5(s-5) | | 4x^2+160=0 | | 24+x=54 | | (fg)(x)=(5x-2)(3x^2) | | 38+5x=-32 | | 6(x-4)+3x=5(2x+8)-14 | | 9x+7=7x+37 | | 12+4q+1=5(q+5) | | c+1-3=-21 |

Equations solver categories